2011
DOI: 10.1111/j.1365-246x.2011.04961.x
|View full text |Cite
|
Sign up to set email alerts
|

On the use of the Norwegian Geotechnical Institute's prototype seabed-coupled shear wave vibrator for shallow soil characterization - II. Joint inversion of multimodal Love and Scholte surface waves

Abstract: SUMMARY Seismic data generated by a novel, seabed‐coupled, shear‐wave vibrator (prototype) and recorded by a densely‐populated, multicomponent ocean‐bottom cable allowed several modes of propagation of Love and Scholte waves to be retrieved in a relatively wide frequency band. Both global dispersion curves and local dispersion curves are extracted in the frequency–wavenumber (f–k) domain and inverted with a multimodal joint Scholte and Love wave inversion algorithm. Monte Carlo inversion is used for a estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…20,21 However, Love-waves are very seldom used in an underwater environment, 7,22,23 since in conventional underwater and seismic experiments sources are deployed in the water column and only Scholte-waves can be generated. In order to generate Love-waves shear-wave sources located on the sea bottom must be used.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 However, Love-waves are very seldom used in an underwater environment, 7,22,23 since in conventional underwater and seismic experiments sources are deployed in the water column and only Scholte-waves can be generated. In order to generate Love-waves shear-wave sources located on the sea bottom must be used.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their field experiences, Eslick et al (2008) concluded that a minimum thickness of 1 m of low-velocity material in the near-surface layer is needed to record usable Love-wave data in the frequency range of interest (5-50 Hz). A multimodal joint Scholte and Love wave inversion using Monte Carlo algorithm was proposed to analyze ocean-bottom data and detected lateral variations of the layer interface depths (Socco et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The work on nonlinear inversion can be found in Ivansson et al (1994), Ohta et al (2008) and Dong & Dosso (2011). More recently Vanneste et al (2011) and Socco et al (2011) used a shear source deployed on the seafloor to generate both vertical and horizontal shear waves in the seafloor. This enabled to measure both Scholte and Love waves and to inverse S-wave speed profile jointly, thereby obtaining information on anisotropy in the subsurface.…”
mentioning
confidence: 99%